Pengembangan Buku Ajar Bidang ilmu Akuntansi Perbankan Kelas XI Semester Genap Berbasis Kontekstual dan Kode Qr di SMK Negeri 1 Lamongan - Dian Rizky Arfiana; Rochmawati Rochmawati (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2023)
Vocational High Schools (SMK) play a role in preparing students to become graduates who are able to enter directly into the world of work and continue on to further higher education. Students, at school get knowledge and learning according to the specialization they take. This study aims to analyze the process of developing textbooks, the feasibility of textbooks, and students' responses to the development of contextual-based textbooks and Qr codes in banking accounting class XI banking and microfinance even semester at SMK Negeri 1 Lamongan. This research method is the development of R&D (Research and Development) with a 4-D development model (Define, Design, Develop, Disseminate) which is carried out until the 3rd stage limit. The results of this study state that 1) contextual-based textbooks and Qr codes are suitable for application in banking accounting learning at SMKN 1 Lamongan, 2) based on the validation results of contextual textbooks and Qr codes developed on banking accounting material for class XI SMKN 1 Lamongan are declared feasible , 3) students are very enthusiastic and feel helped by this contextual-based textbook on banking accounting subjects.